Carbonization of excess sewage sludge using superheated water vapor to produce fuel - Haridan, N. A.; Yoshida, Hiroyuki; Mohd Salleh, Mohamad Amran; Siajam, Shamsul Izhar (IOP Publishing, 2021)
Excess sewage from activated sludge treatment of municipal wastewater is considered one of the most severe solid waste problems. The excess sewage sludge with 64% moisture content was converted to valuable material throughout the superheated water vapor carbonization process. The superheated water vapor carbonized the excess sewage sludge using a bench-scale Rotary Kiln setup to make fuel at 200°C, 250°C, 300°C, 350°C and 400°C. The effect of carbonization with superheated water vapor on the yield and heating value of fuel was studied. In 1 h treatment, organic waste lost about 70% of its original weight due to volatile release during carbonization. The yield of carbonization decreased when the temperature of carbonization increased. A carbon, hydrogen, nitrogen, and sulfur (CHNS) analyzer was used to measure the elemental composition of the carbonized product. The heating value (LHV) of the fuel carbonized at 250°C was 15.0 MJ/kg, determined by a bomb calorimeter. Thus, this study has shown that instead of the landfill, excess sewage sludge can be utilized using superheated water vapor for conversion to fuel.